FAULT-RELATED DOLOMITIZATION WITH HYDROTHERMAL WALL-ROCK ALTERATION IN KINTA VALLEY, PERAK, MALAYSIA. - MOHAMMAD ZAHIR, NURUL AFIQAH (2020)
Thick Devonian-Permian carbonates were deposited on a shallow marine before being uplifted by granitic intrusion during Triassic. These dolomite bodies are commonly found in Kinta Limestone. After the granite intrusion near the Kinta Valley, the residual fluid rose upward through the structure formed especially in deep-seated faults. The existing structures that are present in the host rocks that might controlled the hydrothermal dolomite formation have never been investigated in detail. Besides, dolomite formed in the Kinta Valley was found to be massive and there was a possibility of hydrothermal dolomitization attacked on the host rock which altered it into dolomite.